Does a Spoonful of Sugar Levy Help the Calories Go Down? An Analysis of the UK Soft Drinks Industry Levy - Alex Dickson; Markus Gehrsitz; Jonathan Kemp (Institute of Labor Economics (IZA), 2021)
This study evaluates the effects of the 2018 UK Soft Drinks Industry Levy on soft drinks prices, sales, reformulation activities, and consequently calories consumed. We combine novel electronic point of sale data that cover most of the UK soft drinks market with longitudinal nutritional information and a variety of event-study specifications. We document that all but a few global soft drinks brands reduced sugar content and hence avoided the tiered levy. For brands that maintained their original sugar content, the levy was on average over-shifted resulting in substantial retail price increases. Consumers responded by reducing their consumption of levied drinks by around 18% which is indicative of an inelastic demand response, especially in the drink-now and energy drink segments of the market. We also document substitution into diet drinks in response to the tax. In total, the levy is responsible for a reduction in intake of just under 6,500 calories from soft drinks per annum per UK resident. More than 80% of reductions were due to manufacturers' reformulation activities and occurred in the two years between the announcement of the levy and its implementation.
Keywords: H21; H23; H51; I12; I18; 330; sugar tax; soda tax; reformulation; tax pass-through; sin taxes